O gesto musical de Cristina Dignart em Percussion Mist : trajetória de uma compositora na música mista - Souza, Hyanna Carla Toledo Pereira de (2023)
This dissertation aims to observe and understand the compositional poetics of cuiabana composer Cristina Dignart in her work Percussion Mist (2010), and how her productions contribute to Brazilian electroacoustic music, through the analysis of the musical gesture much discussed in her thesis Space, gesture and texture in electroacoustic music: an analytical and compositional approach. Understanding that musical composition is still a segment considered predominantly male, our objective is to search, through documentary research, in existing data available in articles, books, catalogs and other research, in addition to interviews available on the internet, about life and work by Dignart. Also in observing the possible hegemonic confrontation in their performance due to the social invisibility that women composers in concert music face. Based on reports from other composers, within this same musical segment, we intend to bring important reflection to fuel the debate about gender disparities in the field of contemporary concert music. Additionally, Dignart demonstrates in her work Percussion Mist the creative exploration of sounds with percussion – a solo instrument, together with electronic sounds, suggesting a sound dialogue between acoustic and digital, a field in contemporary music in which works developed by women are rarely seen, or at least there are hardly any records. From this research, with an emphasis on its compositional processes, we will seek, based on the theorists Bério (2015), Berry (1987), Ferraz (1998), Smalley (1986) and Dignart herself (2016), to understand through a musical analysis with computational tools, characteristics of the musical gesture present in Percussion Mist in comparison with the piece Entre Planos (2007) for cello and electronics. This research contributes to the recognition of Cristina Dignart's work within Brazilian electroacoustic music, justifying the academic and social relevance of this dissertation.